2016
DOI: 10.1186/s12935-016-0321-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-210 induces apoptosis in colorectal cancer via induction of reactive oxygen

Abstract: BackgroundDeregulation of miRNA-210 is a common event in several types of cancer. However, increased expression levels in the cancer tissue have been associated with both poor and good prognosis of patients. Similarly, the function of miR-210 with regard to cell growth and apoptosis is still controversial.MethodsOverexpression of miR-210 was performed in HCT116, SW480 and SW707 colorectal cancer (CRC) cell lines. Functional effects of a modulated miR-210 expression were analyzed with regard to proliferation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 73 publications
2
28
0
Order By: Relevance
“…Among those microRNAs presented in our tables, miR-210 overexpression has been shown to increase ROS production in colorectal cancer cells [37, 38]. The augmented ROS can be attributed to compromised mitochondrial activity as miR-210 inhibits mitochondrial iron-sulfur cluster scaffold homologue and the assembly iron-sulfur cluster [37, 39]. MiR-210 also induces ROS generation under hypoxic condition, leading to a poor prognosis in colorectal cancer [37, 38].…”
Section: Aberrant Microrna Profiles and Ros Levels In Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Among those microRNAs presented in our tables, miR-210 overexpression has been shown to increase ROS production in colorectal cancer cells [37, 38]. The augmented ROS can be attributed to compromised mitochondrial activity as miR-210 inhibits mitochondrial iron-sulfur cluster scaffold homologue and the assembly iron-sulfur cluster [37, 39]. MiR-210 also induces ROS generation under hypoxic condition, leading to a poor prognosis in colorectal cancer [37, 38].…”
Section: Aberrant Microrna Profiles and Ros Levels In Colorectal Cancermentioning
confidence: 99%
“…The augmented ROS can be attributed to compromised mitochondrial activity as miR-210 inhibits mitochondrial iron-sulfur cluster scaffold homologue and the assembly iron-sulfur cluster [37, 39]. MiR-210 also induces ROS generation under hypoxic condition, leading to a poor prognosis in colorectal cancer [37, 38]. Furthermore, Tagscherer et al .…”
Section: Aberrant Microrna Profiles and Ros Levels In Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some miRNAs may function as oncogenes or tumor suppressors in tumor development. Furthermore, a widespread down‐regulation of miRNAs is commonly observed in human cancers, which promotes cellular transformation and tumorigenesis . Recent studies have revealed a role of miRNAs in MM.…”
mentioning
confidence: 99%
“…miRNAs serve an important function in the regulation of gene expression by interacting with complementary sites in the 3'-untranslated regions (3'-UTRs) of target mRNAs, inducing translational repression or mRNA cleavage (9). Multiple studies have reported that miRNAs regulate a number of physiological and pathological processes, which include cell proliferation, the cell cycle, differentiation, apoptosis, metastasis, angiogenesis and metabolism (10)(11)(12). miRNAs are involved in tumorigenesis and cancer development, with >50% of miRNAs located at cancer-associated genomic regions (13,14).…”
Section: Introductionmentioning
confidence: 99%